Investigation on the hybridoma cell requirement of glucose and glutamine concentration for growth - Saifuddin , Baharuddin (2013)
A type of monoclonal antibody (MAb) has been developed to diagnose Congenital Adrenal Hyperplasia (CAH). This disease is due to gene effect that causes overproducing of androgen and can cause high mortality of new-born. In order to reduce the death rate of new-born’s due to this disease, large amount of research have been done to produce antibody that can helping the detection of this disease. This research will like to investigate on the hybridoma cells requirement of glucose and glutamine for growth rate and also the effect of the by-products to the growth rate of the cell. Previous study showed that the researcher uses a glucose and glutamine concentration from 2.7 – 24 mM and 4 – 12 mM batch culture. The glucose and glutamine concentration used in this research were varied from 4 – 6 mM and 4 – 5.5 mM respectively. Growth, metabolites consumption (glucose and glutamine) and waste production (lactate and ammonia) were monitored. At the end of this research, the cell growth curve and the specific growth (μ) of each cell culture was determined with the effect of glucose and glutamine as well as lactate and ammonia to the growth of this hybridoma cell. From the results, the maximum cell density achieved at the lowest concentration of glucose and glutamine (4mM) was 7.85 × 105 cells/mL, whereas for the highest was 13.15 × 105 cells/mL. From these results, it shows that low glucose and glutamine concentration could also be sufficient enough to achieve a good and stable growth of hybridoma cell. The maximum μ of 0.2026 h-1was achieved in a medium containing 6mM glucose and 5.5mM glutamine. The glutamine was found to play a major role in the cell growth where it also affects the specific growth rate of the hybridoma cell. The metabolites were determined using YSL biochemical analyser, where it detects glucose, glutamine, lactate and ammonia. Due to equipment breakdown and insufficient time, the ammonia needs to be skipped. The glucose concentration of 6mM in the culture produces maximum concentration of lactate at 10.1mM. The data obtained for ɋglucose, ɋglutamine and ɋlactate was highest at the highest glucose and glutamine concentration (6mM and 5.5mM) where ɋglucose and ɋglutamine were consumed and ɋlactate was produced the most. The glucose (ɋglucose) consumed was -0.0020 nmol/106 cells.hr, glutamine (ɋglutamine) consumed was at -0.0018 nmol/106cells.hr and lactate produced of 0.58 nmol/106 cells.hr. This shows that the feeding of high glucose was not suitable due to high lactate was produced. Thus, the best low concentration to be used for feeding the hybridoma cell was for glucose concentration of 4mM and glutamine concentration of 5.5mM. The result from the experiment shows that at lower glucose concentration, the specific production rate of lactate will decrease as the glutamine concentration increases. It shows that glutamine can act as a carbon source (energy) for the hybridoma cell.A type of monoclonal antibody (MAb) has been developed to diagnose Congenital Adrenal Hyperplasia (CAH). This disease is due to gene effect that causes overproducing of androgen and can cause high mortality of new-born. In order to reduce the death rate of new-born’s due to this disease, large amount of research have been done to produce antibody that can helping the detection of this disease. This research will like to investigate on the hybridoma cells requirement of glucose and glutamine for growth rate and also the effect of the by-products to the growth rate of the cell. Previous study showed that the researcher uses a glucose and glutamine concentration from 2.7 – 24 mM and 4 – 12 mM batch culture. The glucose and glutamine concentration used in this research were varied from 4 – 6 mM and 4 – 5.5 mM respectively. Growth, metabolites consumption (glucose and glutamine) and waste production (lactate and ammonia) were monitored. At the end of this research, the cell growth curve and the specific growth (μ) of each cell culture was determined with the effect of glucose and glutamine as well as lactate and ammonia to the growth of this hybridoma cell. From the results, the maximum cell density achieved at the lowest concentration of glucose and glutamine (4mM) was 7.85 × 105 cells/mL, whereas for the highest was 13.15 × 105 cells/mL. From these results, it shows that low glucose and glutamine concentration could also be sufficient enough to achieve a good and stable growth of hybridoma cell. The maximum μ of 0.2026 h-1was achieved in a medium containing 6mM glucose and 5.5mM glutamine. The glutamine was found to play a major role in the cell growth where it also affects the specific growth rate of the hybridoma cell. The metabolites were determined using YSL biochemical analyser, where it detects glucose, glutamine, lactate and ammonia. Due to equipment breakdown and insufficient time, the ammonia needs to be skipped. The glucose concentration of 6mM in the culture produces maximum concentration of lactate at 10.1mM. The data obtained for ɋglucose, ɋglutamine and ɋlactate was highest at the highest glucose and glutamine concentration (6mM and 5.5mM) where ɋglucose and ɋglutamine were consumed and ɋlactate was produced the most. The glucose (ɋglucose) consumed was -0.0020 nmol/106 cells.hr, glutamine (ɋglutamine) consumed was at -0.0018 nmol/106cells.hr and lactate produced of 0.58 nmol/106 cells.hr. This shows that the feeding of high glucose was not suitable due to high lactate was produced. Thus, the best low concentration to be used for feeding the hybridoma cell was for glucose concentration of 4mM and glutamine concentration of 5.5mM. The result from the experiment shows that at lower glucose concentration, the specific production rate of lactate will decrease as the glutamine concentration increases. It shows that glutamine can act as a carbon source (energy) for the hybridoma cell